Perceptions of HIV cure research among people living with HIV in Australia - Power, J.; Westle, A.; Dowsett, G.; Lucke, J.; Tucker, J.; Sugarman, J.; Lewin, S.; Hill, S.; Brown, Graham; Wallace, J.; Richmond, J. (Public Library of Science, 2018)
Participation in HIV cure-related clinical trials that involve antiretroviral treatment (ART) interruption may pose substantial individual risks for people living with HIV (PLHIV) without any therapeutic benefit. As such, it is important that the views of PLHIV are considered in the design of HIV cure research trials. Examining the lived experience of PLHIV provides unique and valuable perspectives on the risks and benefits of HIV cure research. In this study, we interviewed 20 PLHIV in Australia about their knowledge and attitudes toward clinical HIV cure research and explored their views regarding participation in HIV cure clinical trials, including those that involve ART interruption. Data were analysed thematically, using both inductive and deductive coding techniques, to identity themes related to perceptions of HIV cure research and PLHIV’s assessment of the possible risks and benefits of trial participation. Study findings revealed interviewees were willing to consider participation in HIV cure research for social reasons, most notably the opportunity to help others. Concerns raised about ART interruption related to the social and emotional impact of viral rebound, including fear of onward HIV transmission and anxiety about losing control. These findings reveal the ways in which PLHIV perspectives deepen our understanding of HIV cure research, moving beyond a purely clinical assessment of risks and benefits in order to consider the social context.